The comeback - Chu, Lily (Sourcebooks Casablanca, 2023)
"Ariadne Hui thrives on routine. So what if everything in her life is planned down to the minute: that's the way she likes it. If she's going to make partner in Toronto's most prestigious law firm, she needs to stay focused at all times. But when she comes home after yet another soul-sucking day to find an unfamiliar, gorgeous man camped out in her living room, focus is the last thing on her mind. Especially when her roommate explains this is Choi Jihoon, her cousin freshly arrived from Seoul to mend a broken heart. He just needs a few weeks to rest and heal; Ari will barely even know he's there. (Yeah, right.) Jihoon is kindness and chaos personified, and it isn't long before she's falling, hard. But when one wrong step leads to a shocking truth, Ari finds herself thrust onto the world stage: not as the competent, steely lawyer she's fought so hard to become, but as the mystery woman on the arm of a man the entire world claims to know. Now with her heart, her future, and her sense of self on the line, Ari will have to cut through all the pretty lies to find the truth of her relationship...and discover the Ariadne Hui she's finally ready to be"--